Multiferroic thin films - Sim, Marcus Jun Yi. (2010)
This project addresses the effects of oxygen and deposition pressures on the quality of the BFO thin film produced by PLD. The purpose of this project is to investigate and optimize the experimental conditions to achieve a polycrystalline thin film with a relatively low leakage current. Polycrystalline BFO thin films were fabricated using PLD and its structures were inspected by XRD. AFM/PFM was used to identify the surface topography and domain imaging for the sample. Lastly, a probe station was used to map out the sample’s hysteresis loop and to identify the I-V relationship of the thin film. The results obtained were mostly unsatisfactory and the likely causes of this were the improper preparation of the samples, causing the presence of impurities in the samples. The third sample however, showed a semblance of a hysteresis loop but was ultimately deemed too leaky for any practical usage. Polycrystalline BFO thin films are expected to perform less efficiently than epitaxial thin films. Nevertheless, the leakage current of these thin films can be minimized by means of doping with rare earth materials, or optimizing the deposition pressure during the fabrication step of the sample.